2022
DOI: 10.1002/ana.26419
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Evaluation of Perivascular Space Abnormalities in Neuromyelitis Optica

Abstract: Objective Astrocytes outline the perivascular space (PVS) and regulate fluid exchange through the aquaporin‐4 water channel. As neuromyelitis optica is an autoimmune astrocytopathy targeting aquaporin‐4, we hypothesized that it could be associatied with PVS abnormalities. Methods A total of 34 patients, and 46 age‐ and sex‐matched healthy controls from two independent cohorts (exploratory and validation dataset) underwent a standardized 3.0‐T magnetic resonance imaging protocol including conventional and diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
(104 reference statements)
0
20
0
Order By: Relevance
“…Similar to patients with other diseases, PVS enlargement in the centrum semiovale in patients with neuromyelitis optica spectrum disorder was more severe than that in healthy controls, which was correlated with brain atrophy and poor cognitive performance according to the Paced Auditory Serial Addition Test 3 64 . Additionally, patients with late relapsing–remitting multiple sclerosis (MS) had larger enlarged PVS in the basal ganglia than those with early relapsing–remitting MS and clinically isolated syndrome, and this finding was associated with lesion volume but not with brain atrophy 65 .…”
Section: Measurement Technique For Glymphatic System Activitymentioning
confidence: 61%
See 1 more Smart Citation
“…Similar to patients with other diseases, PVS enlargement in the centrum semiovale in patients with neuromyelitis optica spectrum disorder was more severe than that in healthy controls, which was correlated with brain atrophy and poor cognitive performance according to the Paced Auditory Serial Addition Test 3 64 . Additionally, patients with late relapsing–remitting multiple sclerosis (MS) had larger enlarged PVS in the basal ganglia than those with early relapsing–remitting MS and clinically isolated syndrome, and this finding was associated with lesion volume but not with brain atrophy 65 .…”
Section: Measurement Technique For Glymphatic System Activitymentioning
confidence: 61%
“…22,24 Similar to patients with other diseases, PVS enlargement in the centrum semiovale in patients with neuromyelitis optica spectrum disorder was more severe than that in healthy controls, which was correlated with brain atrophy and poor cognitive performance according to the Paced Auditory Serial Addition Test 3. 64 Additionally, patients with late relapsingremitting multiple sclerosis (MS) had larger enlarged PVS in the basal ganglia than those with early relapsing-remitting MS and clinically isolated syndrome, and this finding was associated with lesion volume but not with brain atrophy. 65 It has also been reported that arterial stiffness was positively and significantly correlated with PVS volume in the basal ganglia, associated with worse cognitive function, including information processing, episodic memory performances, visuospatial performances, and executive function.…”
Section: Perivascular Spacementioning
confidence: 99%
“…Such an association has mostly been studied in stroke, Alzheimer’s dementia, multiple sclerosis, and healthy individuals, yet the data across these studies is inconsistent. Whereas some publications report a negative correlation between MVPVS and various brain volume measures, e.g., in stroke ( Potter et al, 2015b ; Wang et al, 2016 ; Zhang et al, 2016 ), Alzheimer’s disease ( Gertje et al, 2021 ), MS ( Kilsdonk et al, 2015 ; Liu et al, 2022 ), NMOSD ( Cacciaguerra et al, 2022 ), or health ( Chen et al, 2011 ; Sim et al, 2020 ), several studies do not confirm such an association (stroke ( Arba et al, 2018 ), Alzheimer’s disease ( Chen et al, 2011 ), MS ( Wuerfel et al, 2008 ; Conforti et al, 2014 , 2016 ; Favaretto et al, 2017 ; Cavallari et al, 2018 ; Wooliscroft et al, 2020 ; Kolbe et al, 2022 ), and health ( Huang et al, 2021 )).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this inconsistent data, we meta-analyzed correlation in six studies in MS ( Conforti et al, 2014 ; Kilsdonk et al, 2015 ; Favaretto et al, 2017 ; Kolbe et al, 2022 ; Liu et al, 2022 ) and NMOSD ( Cacciaguerra et al, 2022 ) reporting correlation coefficients between MVPVS and brain volume measures (including a total of 258 MS patients and 14 NMOSD patients). The employed MRI parameters for the included studies are summarized in Table 1 (the remaining studies could not be included, either due to missing quantitative data or an insufficient number of publications per disease).…”
Section: Resultsmentioning
confidence: 99%
“…In the pathophysiology of Alzheimer disease, an impairment of glymphatic flow leads to accumulation of b-amyloid and is associated with the progress of cognitive decline. 5,7,11,21,43,46,52,53,57 Likewise, alterations of glymphatic flow are described in Parkinson disease, 15,32,51 in neuroinflammatory 8,9,27 and traumatic disease patterns, 28 as well as in stroke. [16][17][18] The glymphatic system and neuroinflammation in central sensitization may have a reciprocal relationship.…”
mentioning
confidence: 99%